Analytical Assessment of Power of Composite Flash Geothermal Systems - Barbacki, Antoni (Geomatics and Environmental Engineering, 2019)
Analytical formulas make it possible to observe thermodynamic processes without using advanced numerical procedures, as the relationships between the physical parameters become clearly visible. While less accurate, these formulas enable students at the academic research level to quickly and easily model the phenomena using simple calculation programs. For a single-flash system, the linear approximation makes it possible to obtain the expression for the optimum flash temperature and maximal specific power in the assumed temperature interval of geothermal fluid (100‑250°C). These formulas were presented in the author´s previous works. Now, this procedure was used in example analyses for double-flash, combination single & second, and combination single & ORC systems. It was shown that, in the assumed temperature interval of geothermal fluid, the percentage of the additional power of composite-flash geothermal systems is almost a linear function of geothermal fluid temperature as related to a single-flash plant and that the single-flash & ORC cycle gives the highest additional specific power.